Medium as a Character of Victorian Literature in Britain in 1860- 1890s (Proceedings of Southern Federal University. Philology, 2017)
Aelnara T. Akhmedova (Moscow, Russian Federation)The article is devoted to the emergence of a new character in Victorian literature – a medium. The medium was a key figure of Spiritism, popular in the XIX century. In the 1850-1860s it was formed the canonical image of the medium in British periodicals and literature. The article analyzes the characters-mediums in the poetry of R. Browning, novels by E. BulwerLytton and F. Merriet – authors, representing the entire spectrum of spiritualism changes (rejection, skepticism and “research” of interest; a belief in the possibility of communicating with the spirits).Key words: medium, English literature, Victorianism, spiritualism, XIX century, Great Britain.